Europe's forgotten heritage - Razak, Dzulkifli Abd (2011)
IT was less than six months ago, in October 2010, when German Chancellor Angela Merkel affirmed that attempts to build a multicultural society in the country has "failed, utterly failed". Insisting that immigrants should "learn to speak German", she wanted them to do more to integrate.